Additional effect of erenumab for patients with chronic migraine treated with onabotulinumtoxin A—real-world data from a preliminary cohort study - Koelsche, Tristan; Nikolov, Petyo; Koska, Valeria; Ingwersen, Jens; Jansen, Robin; Arat, Ercan; Meuth, Sven G.; Albrecht, Philipp; Lee, John-Ih (Frontiers in Neurology, 2024)
This preliminary retrospective cohort study investigates the potential additive prophylactic effect of erenumab, a fully human monoclonal antibody that blocks the calcitonin gene-related peptide receptor, in combination with ongoing onabotulinumtoxin A (onaBoNT-A) treatment in patients suffering from chronic migraine.The study included 35218 patients and investigated the effects of adding erenumab to the existing treatment regimen. The primary outcome was the MIDAS (Migraine Disability Assessment) score assessed three months after the introduction of erenumab.The results indicated a significant improvement of the MIDAS score, suggesting a reduction in migraine-related disability following the addition of erenumab to onaBoNT-A treatment.onaBoNT-A. In the inter group comparison, dual therapy showed a significantly greater reduction of the MIDAS when compared to a switch from onaBoNT-A to erenumab monotherapy, but not compared to initiation of onaBoNT-A monotherapy. It is hypothesized that the observed additive effects are due to the independent modes of action of erenumab and onabotulinum toxin A.This study suggests that the combination of erenumab with onaBoNT-A may offer an improved approach for the treatment of chronic migraine. in selected patients.However, the results highlight the need for prospective, controlled studies to validate these findings and determine the optimal combination of treatments tailored to the individual patient.